2013
DOI: 10.1590/s0034-71402013000100001
|View full text |Cite
|
Sign up to set email alerts
|

The underpricing of Brazilian IPOs and the adjustment to public and private information

Abstract: JEL Code: G14; G24: G32.This paper examines the underwriters' treatment of information throughout the IPO pricing process based on a sample of Brazilian companies that went public between 2004 and 2011. There is evidence that the offer price partially incorporates the information contained into the Bovespa index during the book-building period, reacting symmetrically to upward and downward movements. The first-day return, as a result, is predictable on the basis of this information. Positive private informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Underpricing of Mauritius listed IPOs examined by Agathee et al (2012) and found that there is a significant positive association of aftermarket risk level, auditors reputation with high initial return and ex-ante financial strength has negative association with high initial return. Further added the idea of underpricing of IPO in Brazil by Avelino (2013) who examined the treatment of information in IPO pricing process comes from the underwriter in Brazil. It is found that information during book building period effect offer price partially upward or downward.…”
Section: Significant Determinants Of Ipos Underpricing In Developing ...mentioning
confidence: 99%
“…Underpricing of Mauritius listed IPOs examined by Agathee et al (2012) and found that there is a significant positive association of aftermarket risk level, auditors reputation with high initial return and ex-ante financial strength has negative association with high initial return. Further added the idea of underpricing of IPO in Brazil by Avelino (2013) who examined the treatment of information in IPO pricing process comes from the underwriter in Brazil. It is found that information during book building period effect offer price partially upward or downward.…”
Section: Significant Determinants Of Ipos Underpricing In Developing ...mentioning
confidence: 99%
“…Avelino (2013) Nesse aspecto, os indicadores de liquidez medem a capacidade de pagamento da empresa do curtíssimo prazo ao longo prazo, comparando-se o que será realizável ao que será exigido (MELO; ALMEIDA; SANTANA, 2012). Ou seja, medem a capacidade da empresa arcar com as suas obrigações financeiras.…”
Section: Ipo Versus Desempenhounclassified
“…Nos anos seguintes, tem-se o desenvolvimento da crise do subprime, que foi uma bolha imobiliária nos EUA que resultou na eclosão de uma crise financeira no âmbito do cenário global (AVELINO, 2013). A crise originou-se nos Estados Unidos e atingiu o mundo, sendo causada por muitos fatores, dentre eles destacamos: "a insolvência dos empréstimos imobiliários subprime, a securitização das hipotecas que estão atreladas a estes créditos e a alavancagem das instituições financeiras" (KREUZBERG; DOCKHORN; HEIN, 2013, p. 5).…”
Section: Introductionunclassified